Analysis of enhancer RNA LINC00910 expression correlating with the immunoregulator STAT3 in glioblastoma cells - E. M. Stasevich; A. V. Simonova; A. N. Uvarova; E. A. Zheremyan; K. V. Korneev; E. A. Bogomolova; D. E. Demin (Медицинская иммунология, 2024)
The transcription factor STAT3 serves as an immunoregulator by playing a crucial role in cytokine receptor signaling. However, in various cancer cell types, STAT3 is involved in the molecular mechanisms of oncogenesis. Specifically, in glioblastoma, the STAT3 immunoregulator has been linked to resistance to temozolomide, the most commonly used chemical agent for treating this type of cancer. Furthermore, literature suggests that activation of this oncogene in glioblastoma cells can significantly impact the tolerogenic tumor microenvironment, weakening the antitumor immune response and contributing to the aggressive course of the disease. Therefore, suppressing STAT3 may not only affect cell growth and resistance to chemotherapy but also enhance the immune response by improving the tumor microenvironment.The development of sequencing technologies has revealed that most of the transcribed material in the cell is noncoding. Long non-coding RNAs are gaining popularity in the study of oncogenesis due to their functional role in the development of various diseases, including oncology. A subtype of long non-coding RNAs transcribed from enhancer elements, known as enhancer RNAs, has garnered attention due to their high specificity in various cells and tissues. Gene co-expression analysis in glioblastoma tumors showed a correlation between STAT3 expression and the enhancer RNA LINC00910, which is located in the same chromosomal domain as the Stat3 gene. Previous literature has shown that LINC00910 is associated with both colorectal and gastric cancer. Additionally, data from the GeneHancer database suggests that the enhancer RNA LINC00910 may be involved in regulating the STAT3 immunoregulator. RNA interference was used to effectively knockdown the enhancer RNA LINC00910, resulting in an 8- to 10-fold reduction in its expression in glioblastoma cell lines. The reduction of LINC00910 expression did not significantly affect Stat3 gene expression in glioblastoma cell lines DBTRG-05MG and U251. This suggests that the correlation between LINC00910 RNA expression and STAT3 gene expression is not due to LINC00910’s direct involvement in STAT3 gene regulation in these cells. Further studies using the selected interfering RNA will help to clarify the role of the enhancer RNA LINC00910 in other signallingsignaling pathways, as well as its potential relationship with cancer development.